Class Management and Teacher Analysis : An Action Research Lesson Study Toward Language Classes (English, Arabic, and Chinese) - Anis, Muhammad Yunus; Malik, Abdul; *, Kristina; *, Karunia (Sebelas Maret University, 2016)
A class in a teaching process has significant role, and also a teacher or a lecturer should manage the class well to get a best teaching process. This teaching process needs an attention to gain the aims of teaching process. So that, to manage the class well regulated, the teacher or lecturer have to do the research lesson (collaborative learning lesson study) to accommodate the factual problems of the class and students. This research will find out the factual problems of language classes, how to build a factual strategy of collaborative learning through lesson study, especially English Class, Arabic Class, and Chinese Class. The dominant factual problems in the language classes will be collected and then analyzed to find the meeting point among the foreign language classes. Thus, the language teachers or lecturers will work together and discuss about solution of problems in the language classroom, and then they should avoid the problems that appear in the class. This research will give some recomendations what should the teacher manage in the language class (Arabic, English, and Chinese Class). The teachers of foreign language can improve the quality of learning and make stronger collegiality among the language teachers. The data in this research will be analyzed by the qualitative method, descriptive analysis. To get the data accurately, the data was taken from the videos and pictures which had been captured during the English Class, Arabic Class, and Chinese Class in the Faculty of Cultural Science (FIB UNS). The result from this research is every single class has a problem with a unique character. This unique character is caused by the divison of language class into a theoritical class and a skill analysis class, such as: conversation class, listening class, writing or composition class, and reading class in English, Arabic and Chinese Language.